Myocardial ischemic tolerance in rats subjected to endurance exercise training during adaptation to chronic hypoxia - Alánová, Petra; Chytilová, Anna; Neckář, Jan; Hrdlička, Jaroslav; Míčová, Petra; Holzerová, Kristýna; Hlaváčková, Markéta; Macháčková, Kristýna; Papoušek, František; Vašinová, Jana; Benák, Daniel; Nováková, Olga; et al. (Journal of applied physiology (1985), 2017)
Chronic hypoxia and exercise are natural stimuli that confer sustainable cardioprotection against ischemia-reperfusion (I/R) injury, but it is unknown whether they can act in synergy to enhance ischemic resistance. Inflammatory response mediated by tumor necrosis factor-α (TNF-α) plays a role in the infarct size limitation by continuous normobaric hypoxia (CNH), whereas exercise is associated with anti-inflammatory effects. This study was conducted to determine if exercise training performed under conditions of CNH (12% O2) affects myocardial ischemic resistance with respect to inflammatory and redox status. Adult male Wistar rats were assigned to one of the following groups: normoxic sedentary, normoxic trained, hypoxic sedentary, and hypoxic trained. ELISA and Western blot analysis, respectively, were used to quantify myocardial cytokines and the expression of TNF-α receptors, nuclear factor-κB (NF-κB), and selected components of related signaling pathways. Infarct size and arrhythmias were assessed in open-chest rats subjected to I/R. CNH increased TNF-α and interleukin-6 levels and the expression of TNF-α type 2 receptor, NF-κB, inducible nitric oxide synthase (iNOS), cytosolic phospholipase A2α, cyclooxygenase-2, manganese superoxide dismutase (MnSOD), and catalase. None of these effects occurred in the normoxic trained group, whereas exercise in hypoxia abolished or significantly attenuated CNH-induced responses, except for NF-κB, iNOS, and MnSOD. Both CNH and exercise reduced infarct size, but their combination provided the same degree of protection as CNH alone. In conclusion, exercise training does not amplify the cardioprotection conferred by CNH. High ischemic tolerance of the CNH hearts persists after exercise, possibly by maintaining the increased antioxidant capacity despite attenuating TNF-α-dependent protective signaling.NEW & NOTEWORTHYChronic hypoxia and regular exercise are natural stimuli that confer sustainable myocardial protection against acute ischemia-reperfusion injury. Signaling mediated by TNF-α via its type 2 receptor plays a role in the cardioprotective mechanism of chronic hypoxia. In the present study, we found that exercise training of rats during adaptation to hypoxia does not amplify the infarct size-limiting effect. Ischemia-resistant phenotype is maintained in the combined hypoxia-exercise setting despite exercise-induced attenuation of TNF-α-dependent protective signaling.
Keywords: TNF-alfa; Nitric Oxide Synthase Type II; Superoxide Dismutase; Myocardial Reperfusion Injury; fyziologická adaptace; kondiční příprava zvířat; superoxiddismutasa; zvířata; Hypoxia; Physical Endurance; NF-kappa B; Adaptation, Physiological; Rats; interleukin-6; synthasa oxidu dusnatého, typ II; mužské pohlaví; Interleukin-6; hypoxie; Tumor Necrosis Factor-alpha; cyklooxygenasa 2; Myocardium; myokard; Cyclooxygenase 2; krysa rodu Rattus; Physical Conditioning, Animal; reperfuzní poškození myokardu; Rats, Wistar; Receptors, Tumor Necrosis Factor, Type II; Animals; Male; receptory TNF - typ II; fyzická vytrvalost; potkani Wistar